Extent of Knowledge of Beekeepers in Relation to Improved Apiculture Practices in Jammu Province - Kumar, Yogesh; Rather, Bashir Ahmad; Peshin, Rajinder; Nain, M.S.; Fatima, Kaneez; Singh, Lokendra; Kanwar, M.S. (Indian Journal of Extension Education, 2020)
The study was conducted to ascertain the knowledge level of beekeepers of Jammu region with respect to the improved beekeeping practices. Four districts were purposively selected for the study which includes Jammu, Kathua, Rajouri and Ramban, due to the maximum number of the beekeepers in these four districts in the Jammu province. The proportionate sampling plan was adopted to select 210 beekeepers. Data was collected with a knowledge test comprising seven improved beekeeping practices. All the districts revealed a significant knowledge gap in all the improved beekeeping practices especially in bee biology, bee enemies, bee breeding and disease management. The marginal beekeepers possessed a low level knowledge regarding these practices. However, the pooled data revealed maximum mean knowledge score with respect to general information followed by management of boxes. The minimum mean knowledge score was recorded in case of knowledge about bee enemies and bee biology. It is concluded that beekeepers of Jammu region had a significant level of knowledge about general beekeeping practices but they were lacking knowledge in some important areas like bee breeding, queen management, bee enemies/disease management and production of other bee products which are important for flourishing the apiculture industry.
Keywords: Bee; Beekeeping; Honey production; Knowledge; Management